Portable Load Monitoring System of Substation Transformer Based on IoT Included GPS - Mahadi Putra, Putu Agus; Rakhmawati, Renny; Aulia, Aura (Politeknik Negeri Ujung Pandang, 2023)
Transformer is a very important thing for distributing electricity. One of the troubles that happen to transformer is overload which can shorten their life or worse case it can cause an explosion. Up until now, PLN Corporation still doesn’t have mitigation alerts for overload. Load monitoring is still done manually along with inputting data on the web. It can cause false inputting of data due to human error. So, this research was made that can be monitored on the web and shown as a diagram with real-time parameters. This research can also be moved to its place because it’s portable. This research uses a current sensor and voltage sensor also GPS which is processed by a microcontroller and then the result is shown in LCD and monitoring web by ESP8266. Hopefully, this research can help PLN mitigate overload and reduce human error, remembering that substation transformer costs a lot. The result of the test shows that this system could read voltage and current values with average sensitivity 0,1803% and 1,15%. Besides, it has GPS to detect location when it moves place and it has high accurate.